If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 2cx(c) + -1c Multiply cx * c 0 = 2c2x + -1c Reorder the terms: 0 = -1c + 2c2x Solving 0 = -1c + 2c2x Solving for variable 'c'. Remove the zero: c + -2c2x = -1c + 2c2x + c + -2c2x Reorder the terms: c + -2c2x = -1c + c + 2c2x + -2c2x Combine like terms: -1c + c = 0 c + -2c2x = 0 + 2c2x + -2c2x c + -2c2x = 2c2x + -2c2x Combine like terms: 2c2x + -2c2x = 0 c + -2c2x = 0 Factor out the Greatest Common Factor (GCF), 'c'. c(1 + -2cx) = 0Subproblem 1
Set the factor 'c' equal to zero and attempt to solve: Simplifying c = 0 Solving c = 0 Move all terms containing c to the left, all other terms to the right. Simplifying c = 0Subproblem 2
Set the factor '(1 + -2cx)' equal to zero and attempt to solve: Simplifying 1 + -2cx = 0 Solving 1 + -2cx = 0 Move all terms containing c to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2cx = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2cx = 0 + -1 -2cx = 0 + -1 Combine like terms: 0 + -1 = -1 -2cx = -1 Divide each side by '-2x'. c = 0.5x-1 Simplifying c = 0.5x-1Solution
c = {0, 0.5x-1}
| -32(15x)+28(24x)= | | a^3+343n^3= | | 6.3x-4+x-1.4= | | -5(-6x+3)= | | -18+7a=2a+3 | | 2p+4(1-p)=4-(2)(1-p) | | 9.5=92.4 | | 0=2xc(x)-x | | 82-115=-8(-4y)-17(2y)+y | | 8x-.2=9.8 | | 80x+40=84x | | Y-8=4(x-5) | | -4i= | | 5x+(-4y)+(-15x)+6y= | | 64+a^6= | | 2y+4x=-1 | | -(2x-5y)= | | 9(2x+10)-7x*4= | | 7(5a+3b)+7(2a+4b)= | | x-18=-1-10 | | -5(4p+3)-31=2(5p+7) | | 8a^3-1= | | 3(3x-9)-2=3(x-5)+16 | | h/15=-7 | | (4x+5)6= | | 4-8n+3n=8-99 | | 9659-268(6)=8262 | | -49+7y+6=2(5y-4)-8 | | 3.2x=-9.6 | | 9[6-(-9x-4)]=729x+378 | | -2x-y=-16 | | -2(x+4)=2x+4 |